Coalition Politics in Contemporary India: Development and Dimensions - SINGH, RAJKUMAR (Universitas Muhammadiyah Yogyakarta, 2019)
Well before the election schedule of India's 17th Lok Sabha to be held ahead of mid 2019 we can not pass any judgement but its coalitional history with varied trends right from the year 1977 and thereafter showed that it is not the cultural homogeneity which is a requisite for political stability and integration, the chances of stable democracy are enhanced to the extent that the group has a number of cross-cutting, politically relevant affiliations. It involves : 1. application of power, in the sense of joint use of resources to determine outcomes'; 2.Â a â€˜mixed motive situation' means the existence of both conflict and cooperation; and 3.Â this is a collective activity, which involves interaction of more than two units. In Indian context it can be safely argued that coalition politics has come to settle at the Indian federal level and that it cannot be viewed as a sudden and unexpected development but on a deeper analysis, it is reflective of a societal metamorphosis: wherein day by day larger number of hitherto latent groups of Indian society are getting mobilised and politicised. Evaluation of coalition politics in India will definitely help many alike countries to set coalitional patterns in the present and the future as well.